THE EFFECTIVENESS OF LISTING AND COMPARING TASKS IN TEACHING TRANSACTIONAL CONVERSATION FOR REFLECTIVE AND IMPULSIVE STUDENTS (The Case of 10th Graders of SMA IbuKartini Semarang in the Academic Year of 2015/2016) - Hardiansyah, Yan; Linggar Bharat, Dwi Anggani (English Education Journal, 2016)
This study was an attempt to test speaking task modelsin teaching transactional conversation for students who have different cognitive styles. These tasksare expected to be appropriatespeaking task models for the students in other to they engage effectively in learning English.This study investigated the effectiveness of listing and comparing tasks in teaching transactional conversation for reflective and impulsive students, the significant differences of achievement between the students by using the listing task and the comparing tasks, discover the significant interaction among the tasks and the cognitive styles in affecting students’ speaking achievement, and the students’ feedback in learning transactional conversation by using the tasks. The research method of this study was quantitativeby using 2x2 factorial experimental research design. The method of collecting the data was observing the cognitive styles of the students, conducting the pre-test and the post-test, and finally givingquestionnaires. After that, the method of analyzing the data used t-test, ANOVA, and triangulation. The results of this study can be concluded that the use of listing task was effective in teaching transactional conversation for the reflective and impulsive students. The result showed that the level of significance by using the listing task and comparing tasks for the reflective and impulsive students was significant because the p values ware smaller than 0.05 (5%). In other hand, the significant difference of achievement between the students by using the listing and comparing tasks were not significant because the p values were greater than 5%. Then, the significant of interaction among the tasks and the cognitive styles in affecting the students’ speaking achievement was not significant because the f-account (1.830) was lower than the t-table (4.098) or it can be assumed that the tasks and the cognitive styles did not affect the students’ achievement significantly.